(untitled) (Biological Sciences - PJSIR, 2002)
The proximate and nutritionally valuable mineral compositions were determined in raw, cooked and fermented Afri can locust bean seeds (ALBS). The functional properties were also evaluated in the fermented sample. Results showed that fermentation improved protein , ash and calcium quantitatively in over cooked sample while fat, carbohyd rate, magnesium, sodium, phosphorus, zinc and iron values were more concentrated in the cooked sample. The functional property results showed that fermented ALBS was poor in most functional properties except i n water absorption capacity. Protein solubility was high in the acid and alkaline media while the isoelectric point was 7.0 showing that fermented ALBS would be useful in food formulations involving both low and high pH.